The granularity of Spanish exports - Juan de Lucio; Raúl Mínguez; Asier Minondo; Francisco Requena (SERIEs - Journal of the Spanish Economic Association, 2017)
Using data for all exporters, we show that it is a small group of firms that dominate exports in Spain. For example, in 2015 the top 200 firms were responsible for half of Spanish exports. This concentration has not changed substantially over the 1997-2015 period. The dominance of a few firms, a phenomenon denoted as granularity, also defines the specialization of Spanish exports. If top exporters disappeared, Spain would lose its revealed comparative advantage in 60% of industries, which account for 45% of all Spanish exports. Finally, granularity explains around one-third of the growth in Spanish exports.
Keywords: F1; F10; F23; 330; Exports; Granularity; Superstars; Spain; Firm-level data